Implementasi Aplikasi Kriptografi Pada Layanan Pesan Singkat (SMS) Menggunakan Algoritma RC6 Berbasis Android - Widi Puji Atmojo; R. Rizal Isnanto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
Security is a very important aspect in data communication. In the last decade, there was a rapid development in mobile phone technology. Smartphone have been equipped with various features and one of them is the short message service (SMS). However, messages sent via mobile phone networks pose threat to be accessed by people who do not have any authorization. Therefore, it is necessary to do research on the development of software to enhance the security of messages through message encryption and decryption features. This application uses Java programming language with SDK (Software Development Kit) Android and Android Studio 1.3.1 as an editor. The initial step of this research is to encrypt the original message to produce the ciphertext message. The second step is to decrypt ciphertext incoming messages to become genuine message. Results from this research are an Android-based application that can perform encryption and decryption of the SMS messages using the RC6 algorithm. With the application of cryptography for SMS messages, the expected level of information security of the message can be improved so that the message will be more secure from unauthorized access.